2016
DOI: 10.1016/j.gerinurse.2015.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Contributing influences of work environment on sleep quantity and quality of nursing assistants in long-term care facilities: A cross-sectional study

Abstract: The effect of shift work on nurses’ sleep is well-studied, but there are other challenging aspects of health care work that might also affect the sleep of direct caregivers. This study examined the influence of the long-term care work environment on sleep quantity and quality of nursing assistants. A cross-sectional survey collected data from 650 nursing assistants in 15 long-term care facilities; 46% reported short sleep duration and 23% reported poor sleep quality. A simple additive index of the number of be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 60 publications
(76 reference statements)
5
32
0
4
Order By: Relevance
“…The JCQ subscales have demonstrated good validity and acceptable reliability in large study populations from six countries (Karasek et al., ). The reliabilities (Cronbach's alpha) of these subscales were .85 (physical demands), .63 (psychological demands), .56 (decision authority) and .75 (social support) for this study sample, which were similar to their reliabilities reported in a previous study with nursing assistants (Zhang, Punnett, Phillips McEnany, & Gore, ). Participants’ usual work shift was collected, and choices were 8 hr day, 8 hr evening, 8 hr night, 12 hr day, 12 hr evening (including work schedules of 9 a.m.–9 p.m. 11 a.m.–11 p.m. and 12 p.m.–12 a.m.) and 12 hr night shifts.…”
Section: Methodssupporting
confidence: 83%
See 4 more Smart Citations
“…The JCQ subscales have demonstrated good validity and acceptable reliability in large study populations from six countries (Karasek et al., ). The reliabilities (Cronbach's alpha) of these subscales were .85 (physical demands), .63 (psychological demands), .56 (decision authority) and .75 (social support) for this study sample, which were similar to their reliabilities reported in a previous study with nursing assistants (Zhang, Punnett, Phillips McEnany, & Gore, ). Participants’ usual work shift was collected, and choices were 8 hr day, 8 hr evening, 8 hr night, 12 hr day, 12 hr evening (including work schedules of 9 a.m.–9 p.m. 11 a.m.–11 p.m. and 12 p.m.–12 a.m.) and 12 hr night shifts.…”
Section: Methodssupporting
confidence: 83%
“…A final limitation was the low reliabilities of the work‐family conflict, psychological demands and decision authority scales in the study sample. Even though the reliabilities of these scales reported in this study were similar to those reported in a previous study with nursing assistants (Zhang et al., ), further assessment and refinement of these scales are needed to improve the internal validity of the study findings.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations